Frequency of Autoimmunity Markers in Type 2 Diabetes - Hameed, Bilal; Niaz, Asif; Khan, Nimra Munir; Nadeem, Maria (Indus Journal of Bioscience Research, 2025)
Background: Type 2 Diabetes (T2D) is associated with various autoimmune markers that may impact disease management and outcomes. Understanding the prevalence of these markers in T2D patients can provide insights into their metabolic profiles and potential complications. Objective: To assess the frequency of autoimmunity markers in patients with Type 2 diabetes. Study Design: Cross-sectional study. Duration and Place of Study: Conducted from December 2024 to April 2025 at the Department of General Medicine, PAF Hospital, Islamabad. Methodology: A total of 369 patients aged 30 to 70 years with a confirmed diagnosis of T2D were enrolled. Blood samples were analyzed for autoantibodies, including Anti-Glutamic Acid Decarboxylase (GAD), Antinuclear Antibodies (ANA), Antiparietal Cell Antibodies (APCA), and Anti-Smooth Muscle Antibodies (SMA). Statistical analyses were performed to assess associations between demographic factors and the presence of autoimmunity markers. Results: The participants had a mean age of 55.7 ± 6.18 years, with 61.5% being male. Among the cohort, 18.2% tested positive for GAD, 26.6% for ANA, 7.3% for APCA, and 4.6% for SMA. Significant associations were found between GAD positivity and older age, male gender, and higher BMI. Conclusion: The study reveals a notable prevalence of autoimmune markers in T2D patients, particularly GAD and APCA. These findings underscore the importance of screening for these autoantibodies in T2D patients to enhance risk stratification and management strategies.